The Shalem Counselling Assistance Plan for Students (CAPS): Delivering Social Work Services to Faith-Based School Systems - Mark Vander Vennen; Marg Smit-Vandezande; Ken Van Wyk; Mikaeli Cavell; Danielle VandenAkker; Richard Csiernik (International Journal of School Social Work, 2022)
In Ontario, Canada, non-Catholic faith-based schools do not receive provincial government funding but are funded primarily by families of students and through fundraising. As a result, historically school-based provision of counselling or school social work resources to students has been the exception rather than the rule, as this has typically been considered an adjunct resource. A new initiative was launched in the province of Ontario in 2011 to address this gap, the Counselling Assistance Plan for Students (CAPS). CAPS was premised on another novel idea, a Congregational Assistance Plan, which itself grew out of concepts derived from Employee Assistance Programming that has roots dating back to the 19th century in Canada. While CAPS has parallels to Student Assistance Programming (SAP), which exists throughout the United States, development of SAP has not taken hold in Canada. This article examines the origins of CAPS, its development, and the nature of assistance it has provided to the schools that have been early adopters.
Keywords: Canada; counselling; faith based schools; school social work; students